2017
DOI: 10.5380/rcc.v9i2.49804
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação das IFRS para pequenas e médias empresas na perspectiva dos prestadores de serviços contábeis

Abstract: ResumoAs mudanças econômicas ocorridas com a internacionalização da economia começaram a demandar uma padronização das normas contábeis entre os países. Nesse sentido, o Comitê de Pronunciamentos Contábeis emitiu o CPC PME -Contabilidade para Pequenas e Médias Empresas correlacionado ao The International Financial Reporting Standard for Small and Medium-sized Entities (IFRS for SMEs) visando a adequação da contabilidade das PMEs aos padrões internacionais. O objetivo deste estudo foi analisar a percepção e apl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
2
0
1
Order By: Relevance
“…Training (between −21.9 pp and −13.5 pp) exhibits an important economic association with non-implementation, indicating to regulators and institutions that education on the standard can be crucial to widespread implementation. This result reinforces previous results from Cavalheiro et al (2017) and Trazzi and Martins (2018). They argue that IFRS for SMEs' subjective aspects are hard to apply and that accountants have little knowledge about the standard.…”
Section: Additional Analysesdeepening the Understanding Of Knowledgesupporting
confidence: 93%
See 1 more Smart Citation
“…Training (between −21.9 pp and −13.5 pp) exhibits an important economic association with non-implementation, indicating to regulators and institutions that education on the standard can be crucial to widespread implementation. This result reinforces previous results from Cavalheiro et al (2017) and Trazzi and Martins (2018). They argue that IFRS for SMEs' subjective aspects are hard to apply and that accountants have little knowledge about the standard.…”
Section: Additional Analysesdeepening the Understanding Of Knowledgesupporting
confidence: 93%
“…This result reinforces previous results from Cavalheiro et al . (2017) and Trazzi and Martins (2018). They argue that IFRS for SMEs' subjective aspects are hard to apply and that accountants have little knowledge about the standard.…”
Section: Resultsmentioning
confidence: 96%
“…For example, Taylor and Zittei (2016) concluded that although Brazilian accounting professionals knew the importance of adopting IFRS, they did not yet have sufficient skills for its de facto implementation; new concepts in the IFRS-based model were poorly mastered and applied by Brazilian accountants in São Paulo. Cavalheiro et al (2017) found that Brazilian accountants struggle with the professional judgment and subjectivity required by IFRS and resist changing the accounting culture; old procedures and habits prevail among accounting professionals at the expense of the new paradigm. The lack of qualified accountants is also identified as the root of many IFRS implementation problems in other emerging economies, including Bangladesh (Nurunnabi, 2017) and Romania (Albu et al, 2014).…”
Section: Perceptions Of Situational Factorsmentioning
confidence: 99%
“…Com isso, o contador, ao invés de executar tarefas operacionais, poderia direcionar seus esforços para melhorar a informação contábil, aplicando seu JDM a questões mais relevantes. Como consequência, no longo prazo, a contabilidade deixaria de ser vista como uma obrigação fiscal (Cavalheiro, Huppes, & Kremer, 2017), para ser considerada peça importante no gerenciamento das organizações. Para tanto, dada a carência, mencionada por alguns dos entrevistados, de materiais explicativos e de cursos ofertados por entidades reguladoras, instituições de ensino e empresas de treinamento, oportunidades de aperfeiçoamento em temas relacionados às IFRS deveriam ser incrementadas.…”
Section: Considerações Finaisunclassified